Learning and Experiencing Intra-active Public Pedagogies in Melbourne’s Laneways: Becoming Part of the Palimpsest - Cooper , Jayson; Sandlin , Jennifer (Journal of Public Pedagogies, 2020)
Through an analysis of street art in Melbourne, Australia, we re-think pedagogies in the interest of publicness as being activist, experimental, and demonstrative, showing how these aspects can be problematised through a new materialist lens. In doing so, we begin to flesh out what we are calling a pedagogy of intra-action. We first briefly define street art, discussing how it has been presented as a democratising practice much in the spirit of Gert Biesta’s ‘pedagogy in the interest of publicness’. We then provide a brief historical overview of street art in Melbourne as well as present some current issues surrounding it. Finally, we consider the phenomenon of street art with new materialist theories, using Karen Barad’s idea of intra-action to re-think Biesta’s ideas about how pedagogies in the interest of publicness are activist, experimental, and demonstrative. In this paper, we seek to further understand Gert Biesta’s pedagogy in the interest of publicness.